The effects of the use of digital technologies and the management of Internet use on psychosocial and behavioral deviations in primary school children - Sabedini, Hekuran; Maksutaj, Mimoza Bytyqi; Shaqiri, Zanfina; Gigollaj, Egzona; Gojani, Leonita (International Journal of Innovative Research and Scientific Studies, 2024)
This study aimed to explore the relationship between internet addiction and psychosocial consequences in primary school students in Pristina. Internet addiction is characterized by compulsive behavior that leads to adverse outcomes, often interfering with crucial aspects of life like work and school. As information technology becomes increasingly integral to society, concerns arise over its overuse, particularly among students, where it can pose a significant risk. The primary objective of this research was to analyze the link between internet addiction and psychosocial consequences for Pristina’s primary school students. A correlational research design was employed to examine whether there is a significant connection between the extent of internet addiction and the resulting psychosocial consequences. Quantitative research methods were integrated into the study’s methodology. Two instruments were used for data collection: the first to measure internet addiction, focusing on students’ internet usage habits, devices employed, and time spent online, and the second to assess psychosocial consequences, encompassing changes in behavior, emotional well-being, and self-esteem attributed to internet usage. The study encompassed 200 primary school students drawn from "Elena Gjika" and "7 Marsi" primary schools in Pristina, aged between 10 and 15, with an average age of 13.18 years. The results showed a positive correlation between internet dependence and psychosocial consequences in students; however, this correlation did not prove to be statistically significant. Moreover, the analysis indicated that there are no differences in the context of internet dependence and psychosocial consequences concerning the gender and age of students in primary schools in Pristina. Similarly, the study among Pristina students in primary school revealed no statistically significant variations depending on age or gender about internet addiction and its psychosocial effects.